2016
DOI: 10.1016/j.clon.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and Head and Neck Cancer: Psychosocial Impact in Patients and Knowledge of the Link – A Systematic Review

Abstract: Head and neck cancer (HNC) currently affects approximately 11 200 people in the UK, with an increasing proportion known to be caused by the human papillomavirus (HPV). We undertook a systematic review of studies measuring the psychosocial impact of HPV-related HNC and also studies measuring knowledge about the link between HPV and HNC among different populations. Searches were conducted on MEDLINE, Embase, PsycINFO, CINAHL Plus and Web of Science, with reference and forward citation searches also carried out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 82 publications
6
28
0
Order By: Relevance
“…Knowledge of the link between HPV and throat cancer was strikingly low, at 11% of the sample. This finding is consistent with a reported range of between 1 and 44% for general (nonmedical or dental professional) population samples in a recent systematic review [32]. Oropharyngeal cancer affects both men and women and is increasing in incidence in several developed countries, including the United States [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…Knowledge of the link between HPV and throat cancer was strikingly low, at 11% of the sample. This finding is consistent with a reported range of between 1 and 44% for general (nonmedical or dental professional) population samples in a recent systematic review [32]. Oropharyngeal cancer affects both men and women and is increasing in incidence in several developed countries, including the United States [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…Our sample also comprised HNC survivors with a wide range of time since the end of their treatment. Emerging research suggests there are core differences between HPV‐ and non‐HPV–related HNC survivors in their QoL; NCRI data relating to HPV was not available to us for HNC cancer survivors at the time of data collection, so we could not explore this. Additionally, 27 consultants (accounting for approximately 10% of HNC survivors meeting our eligibility criteria in Ireland) did not take part in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-one studies were identified which measured knowledge of the link between HPV and HNC, demonstrating the lowest level of knowledge in the general population and highest in medical and dental professionals. 21 However, Signorelli et al showed that only 38% of Italian GPs (n=938) recognised the role of HPV in oral disease and oral cancer and concluded that there is a lack of knowledge on HPV infection and vaccination in Italian GPs. 22 Odone et al explored reasons for non-vaccination against HPV in Italy, 23 providing a useful basis to plan, implement and evaluate targeted educational programmes and training.…”
Section: Discussionmentioning
confidence: 99%